Antarctic coastal microalgal primary production and photosynthesis - McMinn, A; Ashworth, C; Bhagooli, R; Martin, A; Salleh, S; Ralph, P; Ryan, K (2012)
Primary production in coastal Antarctica is primarily contributed from three sources: sea ice algae, phytoplankton, and microphytobenthos. Compared to other eastern Antarctic sites, the sea ice microalgal biomass at Casey Station, in spring 2005 was relatively low, 3.84 ± 1.67 to 21.6 ± 13.3 mg chl-a m-2 but productive, 103-163 mg C m-2 day-1. The photosynthetic parameters, Fv/Fm and rETRmax, imply a community well-acclimated to the light climate of the benthic, water column, and sea ice habitats. Phytoplankton biomass was greatest in late spring (11.1 ± 0.920 μg chl-a l-1), which probably reflects input from the overlying sea ice. Lower biomass and depressed Fv/Fm values later in the season were probably due to nutrient limitation. Benthic microalgal biomass was consistently between 200 and 400 mg chl-a m-2 and production increased through into late summer (204 mg C m-2 day-1). After the sea ice broke out, the marine environment supported a small phytoplankton biomass and a large benthic microalgal biomass. Compared with previous studies, Fv/Fm values were relatively low but there was no evidence of photoinhibition. When sea ice was present, primary production of benthic microalgae was either very low or there was a net draw down of oxygen. The benthic microalgal community made a larger contribution to total primary production than the phytoplankton or sea ice algae at water depth less than approximately 5 m. © 2012 Springer-Verlag.